The foundation of the Confederation of Mexican Workers (Tzintzun, Revista de Estudios Históricos, 2016)
The article argues that the Mexican leader and politician, Vicente LombardoToledano, who dedicated his life to the creation of labor unions, newspapers,workers’ universities, magazines and parties, held a concept of popular democracywhose axis and executor was the State. he methodological focus to elaboratethe arguments of this article is not only social and political history butalso the biography with which it is articulated. he articulation of history andbiography grants a subjective dimension to the projection of the individual inthe trajectory of his times. he article is based primarily on the archive of LombardoToledano and combines information from this archive with other archives,permitting one to reexamine the relations between Lombardo Toledanoand the Mexican Communist Party, the compromises between him and FidelVelázquez and the methods to achieve the ctm’s penetration in the country’sstates. Ultimately, the problem that the article discusses is worker’s democracyand union autonomy.
Keywords: Vicente Lombardo Toledano; Confederation of Mexican Workers; labor unions; democracy